ANALYSIS OF THE IMPLEMENTATION OF ABANDONED LAND CONTROL IN BEKASI REGENCY - Yayas Nabila Faraz Yuliansari; Yayas Nabila Faras Yuliansari (Journal Social Sciences and Humanioran Review, 2024)
Land rights must be protected by the state and society. Land rights must be registered in order to provide legal certainty for rights holders. However, in practice there are many lands that are registered but not used according to their designation. Not utilizing the land in accordance with the designation which makes abandoned land cause losses not only to rights holders, but also to the loss of the community and the state. The method in this study is juridical Normative. The results of this study are that soil has an important role in development dynamics. The importance of the role of land in having a legal relationship with its rights holders. Land that already has rights must be allocated as it should. The amount of land that is registered but not used according to its designation. Almost all of the land that is indicated to be abandoned exists in various provinces and districts/cities throughout Indonesia.